Optimalisasi Teknologi Tepat Guna dan Platform Digital pada Pengrajin Kain Tradisional Sasirangan - Sri Hartini; Dewi Dewantara; Mahmudah Hasanah; Selvia Dina Norzahidah; Selvina Agustin (Jurnal Pemberdayaan Masyarakat, 2026)
Ecomel Sasirangan, a partner of the Community Service team from Universitas Lambung Mangkurat, faced significant challenges in production and marketing. To address these challenges, the community service team implemented a program focused on increasing production capacity while strengthening marketing strategies through optimizing appropriate technology and digital platforms. Activities included outreach, training, technology implementation, mentoring, evaluation, and planning for program sustainability. The results of the activities showed positive achievements, marked by the development and implementation of an e-inventory website (https://app.ecomelsasirangan.com/) and a sasirangan fabric dyeing tool to increase production capacity, and the launch of an e-catalog website (https://ecomelsasirangan.com/) to support marketing. The implementation of the e-inventory and the sasirangan fabric dyeing tool facilitated partners in production planning and evaluation, while the e-catalog could expand market reach and acquire new consumers. Thus, the implementation of appropriate technology successfully increased the effectiveness of production and marketing at Ecomel Sasirangan. In an effort to support the development of Ecomel Sasirangan and increase community involvement in general, this program has opportunities for further development.